Ergonomics, anthropometrics, and kinetic evaluation of gait: A case study - Lima, Rosa (2015)
This study aimed to develop appropriate changes in a pair of shoes in order to improve the gait of an individual selected for this case study. This analysis took into account ergonomic aspects, namely those relating to the individual’s anthropometrics. Gait analysis was done with the adapted footwear both before and after intervention.A conventional X-ray was performed, which revealed a 29-mm left lower limb shortening and possible foot adduction. The anthropometric assessment confirmed a 27-mm asymmetry between the left knee and foot.Corrective changes were implemented in the left boot, with a 20-mm increase in the plantar aspect and approximately 30-mm in the calcaneus area.The pressure-mapping system WalkinSense was used for the kinetic gait analysis. Results showed some improvement in plantar pressure distribution after corrective changes in footwear. Peak pressure in the left foot decreased from 2.8kg/cm2 to 1.6kg/cm2. The second peak also showed a marked decrease. The right foot presented with a reduction in peak plantar pressure from 2.7kg/cm2 to 2.3kg/cm2.After identifying asymmetries, the associated pathologies and modifyingthe footwear, a kinetic analysis of gait before and after altering the footwear was undertaken, which showed improvements in the gait. According to the obtained results, it was possible to demonstrate that the initially proposed objectives were achieved, i.e., the changes in footwear resulted in an improvement of the analyzed individual.